2020
DOI: 10.1103/physreve.101.042114
|View full text |Cite
|
Sign up to set email alerts
|

One-step replica-symmetry-breaking phase below the de Almeida–Thouless line in low-dimensional spin glasses

Abstract: The de Almeida-Thouless (AT) line is the phase boundary in the temperature-magnetic field plane of an Ising spin glass at which a continuous (i.e. second-order) transition from a paramagnet to a replica-symmetry-breaking (RSB) phase occurs, according to mean-field theory. Here, using field-theoretic perturbative renormalization group methods on the Bray-Roberts reduced Landau-Ginzburg-type theory for a short-range Ising spin glass in space of dimension d, we show that at nonzero magnetic field the nature of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Hence, if other kinds of phase transitions (dynamical, first order, etc.) were present (as suggested by Höller and Read [ 38 ]), we could miss them. We consider this new scenario very interesting, and we are considering studying it, but with a different numerical approach.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, if other kinds of phase transitions (dynamical, first order, etc.) were present (as suggested by Höller and Read [ 38 ]), we could miss them. We consider this new scenario very interesting, and we are considering studying it, but with a different numerical approach.…”
Section: Discussionmentioning
confidence: 92%
“…The existence (or not) of the spin-glass condensation in the presence of a magnetic field remains the subject of some controversy (see, e.g., [56][57][58][59]). In a mean-field treatment, de Almeida and Thouless [60] showed that, for the Sherrington-Kirkpatrick infinite-range mean-field model [61], there would be a phase transition according to the following relationship for Ising spin glasses,…”
Section: Investigation Of the Dat Line In D =mentioning
confidence: 99%
“…In previous work, Höller and the author [9] (we refer to this paper as HR), building on the notions of complexity from Refs. [5,6] but using the spin distribution restricted to a finite window Λ W , arrived at a definition of complexity, relative to the window, of an infinite-size Gibbs state (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This definition has several desirable properties, and in some situations it reduces to the entropy of the set of weights of pure states as W → ∞. For Ising spins and nearest-neighbor interactions it was easy to show [9] that it is less than a constant times the surface area ∼ W d−1 of the window, for any temperature T ≥ 0.…”
Section: Introductionmentioning
confidence: 99%